Financial strategy and the process of the internationalization of enterprises - Różański, Jerzy; Bogołębska, Justyna (Strategia finansowa a proces internacjonalizacji przedsiębiorstw, 2020)
The article presents preliminary research on the financial strategy of enterprises in the process of internationalization. Using the survey as a research method, 25 enterprises that export their products outside Poland were examined. The main hypothesis is that the economic crisis caused by the pandemic will not lead to a change in the significance of factors influencing the enterprises’ financial strategy, and in particular to the change in the relationship between internationalization and an enterprise’s financial strategy
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 4, s. 55-65
Keywords: internationalization; enterprise; financial strategy; internacjonalizacja; przedsiębiorstwo; strategia finansowa